International financial markets - Fung, Hung-gay; Tse, Yiuman (Frontiers of economics and globalization ;, 2013)
In recent years, the globalization of financial asset markets has become increasingly important and has led to closer linkages among these markets. New global investment instruments such as sovereign credit default swaps, exchange traded funds, and bond markets have been created, enabling investors to fine tune their investment portfolios to their likings. Financial investments have been further expanded to include real asset investments such as real estate investments. It is important for global investors to make proper decisions in assessing these investments in their asset allocations and for policymakers who can provide sound policy guidance to cope with the globalization of the financial markets. This volume contributes to a fresh perspective on the economic and finance research on international financial markets and also the commodity markets. It enables scholars, policymakers, and practitioners to better understand the changes and dynamics of commodity and financial asset trading following the recent global financial crisis. This volume contains a comprehensive analysis of international financial markets through a series of essays from leading researchers in the field.